Efficacy and safety of biosimilar rituximab in patients with pemphigus vulgaris: a prospective observational study. (2nd January 2021) - Toosi, Roja; Mahmoudi, Hamidreza; Balighi, Kamran; Teimourpour, Amir; Alaeen, Hoorieh; Shaghaghi, Mohammadreza; Abedini, Robabeh; Daneshpazhooh, Maryam
Abstract: Background: The optimal treatment for pemphigus vulgaris (PV) has not been clearly determined yet. Rituximab (RTX) was recently approved for the management of adults with moderate to severe PV. Objectives: This prospective observational study was designed to evaluate the efficacy and safety of biosimilar RTX in PV patients. Methods: The efficacy and safety were evaluated by assessing the pemphigus disease area index (PDAI) score, clinical response and any adverse events (AEs) during at least 12-month follow-up. We evaluated anti-desmoglein (Dsg) 1, 3 level at baseline, 3 months and 12 months after RTX infusion. Results: A total of 110 patients treated with biosimilar RTX were enrolled between May 2016 and July 2017. The mean age was 43.58 ± 11.77 years and the mean follow-up time was 16.22 ± 3.45 months. A notable decrease in PDAI score, anti-Dsg 1, 3 level and prednisolone dosage was observed. Median delay to achieve complete remission (CR), median duration of CR, and median time to relapse were 3, 9, and 12 months, respectively. Newly diagnosed patients (NDPs) experienced higher rate of CR, longer duration of remission and lower risk of relapse, compared to previously treated patients (PTPs). A total of 47 AEs were observed in 33 (30%) patients, which were mostly mild infusion-related reactions. Conclusion: Administration of biosimilar RTX in PV patients was associated with desirable outcomes in terms of efficacy and safety in both NDPs and PTPs.First-line use of RTX in NDPs was more effective and allowed a rapid tapering of corticosteroid doses compared to PTPs.